Multiscale Method for Seismic Response of Near-Source Sites - Shutao Li; Jingbo Liu; Zhou Yang; Xin Bao; Fei Wang; Xiaofeng Wang; Mohsen Saleh Asheghabadi (Advances in Civil Engineering)
The traditional source-site-structure model for the calculation of seismic response of underground structures at near-source sites is restricted by the grid scale and the size of the structure. As a result, an excessive number of elements in the model make the numerical solving process difficult. To solve problems such as an inefficient computation and challenging nonlinear simulation, a multiscale analysis method for the calculation of the seismic response of underground structures at near-source sites is developed. The generalized free-field seismic response of the near-source region is obtained by establishing a large-scale calculation model of the source site and is used to simulate the fracture mechanism of faults and the process of seismic wave propagation. Then, using the method of seismic wave input based on artificial boundary substructures, the free-field motion of the wave is transformed into the equivalent seismic load, which is the seismic wave input data for the small-scale region of interest. Finally, with the help of local elements with special shapes to realize the grid transition of different scales, a small-scale model with reasonable soil-underground structure interaction is established, and the seismic response of the overall model can be effectively solved. The calculation and analysis of the seismic response of underground structures in irregular terrain are carried out. Compared with the results obtained directly from the source-site-structure model, the multiscale method has satisfactory accuracy and meets the needs of engineering design. Since the number of elements is fewer and the calculation time is much shorter than those required by the traditional model, the advantages in computational efficiency of the new method are highlighted. In addition, the reflected waves are too weak to have a considerable impact on structures because of the great energy loss at the reflection interface, which further proves the feasibility of the closed artificial boundary substructure method.